Portal vein thrombosis in a complicated case of Crohn's disease. Issue 798 (April 1992) - Crowe, A.; Taffinder, N.; Layer, G. T.; Irvine, A.; Nicholls, R. J.
Abstract : Portal vein thrombosis is a rare complication of ulcerative colitis and is invariably fatal. This report describes a patient with severe Crohn's disease who underwent elective surgery complicated by an anastomotic disruption with faecal peritonitis. Following emergency laparotomy he developed left hypochondrial pain which was a manifestation of splenomegaly consequent upon portal vein thrombosis. Anticoagulation was successful in preventing further spread of the thrombosis as monitored by colour Doppler ultrasound. Severe active disease, surgery and sepsis have been recognized as predisposing factors for thromboembolic complications in inflammatory bowel disease and this patient was exposed to all three. It is conceivable that portal vein thromboses occur more commonly than suspected and ultrasound scanning could ascertain the prevalence if performed prospectively.